2018
DOI: 10.1128/aem.02858-17
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in PGM2 Causing Inefficient Galactose Metabolism in the Probiotic Yeast Saccharomyces boulardii

Abstract: The probiotic yeast has been extensively studied for the prevention and treatment of diarrheal diseases, and it is now commercially available in some countries. displays notable phenotypic characteristics, such as a high optimal growth temperature, high tolerance against acidic conditions, and the inability to form ascospores, which differentiate from The majority of prior studies stated that exhibits sluggish or halted galactose utilization. Nonetheless, the molecular mechanisms underlying inefficient galacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 48 publications
5
50
0
Order By: Relevance
“…More likely, it is produced to prevent the intracellular accumulation of galactose-1-phosphate, a phosphorylated intermediate of the Leloir pathway (Fig. 5), which is toxic to the cell [44, 46]. The efficient utilization of galactose is limited by conversion of galactose-1-phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…More likely, it is produced to prevent the intracellular accumulation of galactose-1-phosphate, a phosphorylated intermediate of the Leloir pathway (Fig. 5), which is toxic to the cell [44, 46]. The efficient utilization of galactose is limited by conversion of galactose-1-phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…3B). In fact, it has been reported that Pgm2 is a rate-limiting enzyme [21] and its overexpression can significantly improve galactose metabolism in S. cerevisiae [22][23][24]. Moreover, previous studies have also demonstrated that Rho1 acts as molecular switches to multiple stress conditions [25] and is involved in regulation of cell wall biogenesis in S. cerevisiae [13,14].…”
Section: Optimization Of β-Glucan Biosynthesis Pathway To Enhance Glumentioning
confidence: 99%
“…Phosphoglucomutase is responsible for converting glucose-1-phosphate to glucose-6-phosphate and LiCl is an inhibitor of its enzymatic activity. When galactose is used as the carbon source, inhibition of phosphoglucomutase by LiCl results in the accumulation of galactose metabolite intermediates that in turn causes growth defects [11,12]. In the presence of glucose, LiCl reduces the levels of UDP-glucose and disrupts the associated pathways.…”
Section: Introductionmentioning
confidence: 99%